(untitled) (Research, Society and Development, 2020)
The control of food losses and wastage is relevant from the economic point of view, in relation to combating hunger and improving food security. The objective of this study was to evaluate the food waste and to identify and quantify fruit and vegetable processing waste in self-service commercial restaurants at Rio de Janeiro State University, to compare the data of this research with other studies, and to present strategies for the minimization and reutilization of residues. For the analysis of the discarded leftovers, gastronorms with food were weighed, discounting the value of the container. For food scraps quantification the remaining food on the plate was quantified. Residues from fruit and vegetable (which ones?) processing was weighed separately. To evaluate the monetary value lost with the leftover, food weight price charged to consumers (R/kg) was multiplied by leftover value. Data were analyzed by analysis of variance (ANOVA) followed by Tukey’s post-test (p≤0.05), using software Excel 365 (Microsoft®) and PAST 3.2. The three restaurants presented intact per capita intake within the usual values. However, the surplus discarded per capita was higher than what is recommended and Restaurant 1 presented greater monetary loss with this surplus. In Restaurant 1, the sum of fruit and vegetable waste accounts for more than 50% of total organic waste. The food waste represents a worrisome scenario from a social, economic and environmental point of view. In this sense, public policies are necessary to increase conditions to access food, to stimulate whole food utilization and to reduce food waste.